Decreased Peripheral Mitochondrial DNA Copy Number is Associated with the Risk of Heart Failure and Long-term Outcomes. Issue 15 (April 2016) - Huang, Jin; Tan, Lun; Shen, Rufei; Zhang, Lina; Zuo, Houjuan; Wang, Dao W.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Mitochondrial DNA (mtDNA) copy number variation (CNV), which reflects the oxidant-induced cell damage, has been observed in a wide range of human diseases. However, whether it correlates with heart failure, which is closely related to oxidative stress, has never been elucidated before. We aimed to systematically investigate the associations between leukocyte mtDNA CNV and heart failure risk and prognosis. A total of 1700 hospitalized patients with heart failure and 1700 age- and sex-matched community population were consecutively enrolled in this observational study, as well as 1638 (96.4%) patients were followed prospectively for a median of 17 months (12–24 months). The relative mtDNA copy number of leukocyte of peripheral blood or cardiac tissue was measured in triplicate by quantitative real-time PCR method. Patients with heart failure possessed much lower relative mtDNA copy number compared with control subjects (median 0.83, interquartile range [IQR] 0.60–1.16 vs median 1.00, IQR 0.47–2.20; P  < 0.001), especially for the patients with ischemic etiology (median, 0.77 for ischemic and 0.91 for non-ischemic, P  < 0.001). Patients with lower mtDNA copy number exhibited 1.7 times higher risk of heart failure (odds ratio 1.71, 95% confidence interval [CI] 1.48–1.97, P  < 0.001). Long-term follow-up (median of 17 months) showed that decreased mtDNA copy number was significant associated with both increased cardiovascular deaths (hazard ratio [HR] 1.58, 95% CI 1.16–2.16, P  = 0.004) and cardiovascular rehospitalization (HR 1.48, 95% CI 1.21–1.82, P  < 0.001). After adjusting for the conventional risk factors and medications, lower mtDNA copy numbers were still significantly associated with 50% higher cardiovascular mortality ( P  = 0.035). In conclusion, mtDNA copy number depletion is an independent risk factor for heart failure and predicts higher cardiovascular mortality in patients with heart failure.